A comparison between liquid group A plasma and thawed group A plasma for massive transfusion activation in trauma patients. Issue 4 (2nd November 2021) - Fadeyi, Emmanuel A.; Saha, Amit K.; Soltani, Sohaila; Naal, Tawfeq; Palmer, Robert; Bakht, Azad; Warren, Christina S.; Simmons, Julie H.; Pomper, Gregory J.
Abstract: Background and Objectives: The use of group A thawed 24‐h plasma when resuscitating haemorrhagic shock patients has become more common; however, limited data exist on the clinical use of liquid plasma (LP). Our aim is to determine whether LP is of clinical benefit to patients requiring massive transfusion. Materials and Methods: The objective of this retrospective study was to detect any difference in 24‐h survival between patients receiving liquid or thawed plasma (TP) during their massive transfusion activation. Other objectives were to report any difference in hospital length of stay (LOS), intensive care unit (ICU) LOS and in‐hospital survival. Data collected included gender, age, mechanism of injury, Injury Severity Score, Revised Trauma Score and Trauma Injury Severity Score. Results: A total of 178 patients received 1283 units of LP, median 4 and range (1–56), whereas 270 patients received 2031 units of TP, median 5 and range (1–87). The two study groups were comparable in terms of gender, age, mechanism of injury, whole blood, red blood cells, platelets and cryoprecipitate transfused. The use of LP during the massive transfusion activation in traumatically injured patients was not associated with increased 24‐h survival compared to when using TP, p = 0.553. Conclusion: Our study did not show a difference in 24‐h or 30‐day survival between the use of LP compared to TP in trauma patients. LP should be considered an alternative to TP in trauma patients requiring immediate plasma resuscitation.